The Effect of Free Shipping Promotion Strategy (Ongkir), Cash on Delivery (COD) Payment Method, and Flash Sale on Purchasing Decisions for Shopee Users in Bandar Lampung City - Cucu Dina Mustika Ratu; M. Oktaviannur (International Journal of Economics, Business and Innovation Research, 2024)
This study aims to determine the effect of the Free Shipping Promotion Strategy (Ongkir), the Cash on Delivery (COD) Payment Method, and flash sales on Shopee sales in Bandar Lampung. The method used in this research is the descriptive quantitative method. Purposive sampling is used, with a sample size of around 97 respondents. The data analysis technique uses multiple-line regression analysis. Based on the results of the t-test, it was found that the Free Shipping variable did not significantly affect the process of determining the purchase intention of Shopee users in Bandar Lampung city. Conversely, the Cash-on-delivery and flash-sale variables significantly affect Shopee users' modification of their purchase order in Bandar Lampung. Conversely, the cash-on-delivery and flash sale variables significantly affect Shopee users' purchasing decisions in Bandar Lampung city. Based on the coefficient of determination test, which results in an R Square value of 0.628, the free shipping, Cash on delivery, and flash sale variables affect the purchasing decision variable by 62.8%, with the remaining 37.2% being influenced by variables not examined in this study.